Vista Inovasi Kurikulum yang Diterapkan di SMPIT at-Taqwa Surabaya - Merduani, Frestinata Arum; Nafisah, Lu’luatun; Sya’diyah, Khalimatus; Mahardika, Ahmad Reza Bayu; Amalia, Kaniati (ALSYS, 2024)
The aim of this research is to find out more about the typical curriculum used by At-Taqwa Integrated Islamic Middle School, namely the VISTA Curriculum, and what stages they carry out starting from socialization, planning, implementation, to the evaluation stage. The research method used in writing this article is through a qualitative approach using data collection through direct observation at the research location and systematic library observation or what is commonly known as SLR, which is a method of collecting literature or theories related to paper. from various sources such as books, journals, scientific articles and other sources related to the research topic. The research results show that the use of the VISTA Curriculum in the school went well from the socialization to evaluation stages and succeeded in producing a superior generation, both in the fields of academics, character and religion.